The Coordination Pyramid: A Perspective on the State of the Art in Coordination Technology - Sarma, Anita; Van der Hoek, Andre; Redmiles, David (Computer (Long Beach, Calif.), 2019)
Any software development project uses software tools that assist its developers in coordinating their efforts. These tools, termed coordination technologies in this paper, have undergone remarkable changes over time in the functionality that they offer. We contribute a novel perspective on this historical trend with our Coordination Pyramid, a framework that recognizes four distinct paradigms of coordination and classifies coordination technologies according to which paradigm they primarily support. Although historical in its construction, the Pyramid has strong implications for both current practice and future re-search directions. With respect to practice, the Pyramid helps organizations in identifying and articulating future coordination needs, mismatches that exist between these needs and the portfolio of coordination tools presently in use, and solution strategies for addressing these mismatches. With respect to research, the Pyramid clearly highlights several trends in how tools have historically evolved and can be anticipated to evolve in future.